1983
DOI: 10.1111/j.1469-8749.1983.tb13743.x
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Isokinetic Strengthening Program for Patients with Severe Hemophilia

Abstract: SUMMARY A modified isokinetic strengthening program for the knee flexors and extensors was evaluated in 32 patients with severe hemophilia. The program was effective in significantly strengthening the knee flexors and extensors; it did not increase the number of knee hemarthroses; and it could be done at home without special equipment. The greater increases in extensor and flexor strength among adolescents and adults were associated with less severe arthropathy, a l cm increase in thigh girth, and a greater nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 10 publications
(4 reference statements)
1
48
0
2
Order By: Relevance
“…Table shows the quality assessment of the five non‐randomized studies according to the MINORS tool. The mean MINORS score was 16/24 for the comparative controlled trial and 10/16 (range 7‐12/16) for the four single‐group prospective studies . The majority of the studies reported adequately on a clearly stated aim (5/5), on the inclusion of consecutive patients (3/5), on a prospective collection of data (5/5), on endpoints (4/5) and on a follow‐up period (5/5) appropriate to the aim of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table shows the quality assessment of the five non‐randomized studies according to the MINORS tool. The mean MINORS score was 16/24 for the comparative controlled trial and 10/16 (range 7‐12/16) for the four single‐group prospective studies . The majority of the studies reported adequately on a clearly stated aim (5/5), on the inclusion of consecutive patients (3/5), on a prospective collection of data (5/5), on endpoints (4/5) and on a follow‐up period (5/5) appropriate to the aim of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that they included inhibitor patients in their active groups . Age ranged between seven and 66 years. Patients received factor replacement therapy either prophylactic or on demand, three studies did not report on the factor therapy .…”
Section: Resultsmentioning
confidence: 99%
“…Las primeras investigaciones fueron publicadas en los años ochenta, y desde entonces y hasta el final del pasado siglo, tan sólo encontraron cinco investigaciones, de las que lo más destacable es que todas ellas realizaron una intervención dirigida a la mejora de la fuerza 35,[78][79][80][81] (tabla 2). Una de ellas también incluyó el entrenamiento postural y otra investigación unió al entrenamiento de fuerza actividades deportivas (carrera, ciclismo y natación).…”
Section: Estudios Experimentales Sobre La Condición Física En El Paciunclassified
“…A set of exercises, preferably where the whole family joins in, can be performed daily at home. Exercise is the cheapest, but most ignored, form of prophylactic care for haemophilia 3 .…”
Section: Preventive Carementioning
confidence: 99%
“…Whether used to treat spontaneous oral haemorrhages or to prevent bleeding from dental procedures in patients with haemophilia A or B, either drug is begun in conjunction with DDAVP or factor-replacement therapy and continued for 2-5 days or until mucosal healing is complete 3 . These drugs are contraindicated in the presence of haematuria, for clots in renal tubules may not be resorbed in the presence of inhibitors of fibrinolysis.…”
Section: Antifibrinolytic Therapymentioning
confidence: 99%